Design, complexing and catalytic properties of phosphorus thiazoles and benzothiazoles: a concise overview. (17th October 2019) - Majoral, Jean-Pierre; Zablocka, Maria; Koprowski, Marek; Hameau, Aurelien; Shi, Xiangyang; Mignani, Serge; Caminade, Anne-Marie
Abstract : Playing with the versatile reactivity of thiazole and phosphorus derivatives leads to active ligands and complexes in catalysis. Abstract : The versatile functionalization of thiazoles and benzothiazoles at different locations in their backbone offers the possibility to design many substituted heterocyclic derivatives bearing active groups for applications in coordination chemistry, catalysis, and medicinal chemistry. The grafting of various phosphorus groups (phosphines, phosphine oxides, phosphonates, phosphinic acids, etc. ) via different strategies leads to many phosphorus thiazoles and benzothiazoles acting per se as catalysts for a number of reactions for complexation with metals such as Ir, Au, Pt, Pd, and Cu, for which the catalytic properties were investigated.